EFEK KATETER TERHADAP FUNGSI PSA SERUM SEBAGAI PREDIKTOR VOLUME PROSTAT PADA PASIEN YANG TERBUKTI BENIGN PROSTATIC HYPERPLASIA PADA PEMERIKSAAN HISTOPATOLOGIS - Tranggono, Untung; Mochtar, Chaidir A; Umbas, Rainy (Indonesian Urological Association, 2009)
Objective: To define the use of Prostate Specific Antigen (PSA) as a predictor of prostate volume in catheterized BPH patients. Material & methods: Data were collected from medical record of symptomatic BPH patients who underwent prostate biopsy at Cipto Mangunkusumo Hospital Urology Clinic since 1994 until 2006. Data of age, serum PSA, indwelling catheter, maximal flow, urine residue, and prostate volume were recorded as variables. Patients who had histopathological result of BPH with or without prostatitis were included; while who had prostate carcinoma, high grade prostatic intraepithelial neoplasm (HGPIN), and BPH with atypical small acinar proliferation (ASAP) were excluded. Subject were then divided into 2 groups, catheterized or not. Data were analyzed using Mann-Whitney test, analysis of variance, correlation test and linear regression test. Results: Of 2283 patients were performed prostate biopsy, 1036 patients had results of BPH with or without prostatitis, 766 patients had prostate carcinoma, while 581 patient’s biopsy result were not recorded. Of the 1036 patients, 347 were catheterized, 192 non-catheterized, and 457 were not recorded. In the catheterized group the average age were 67,04 years old, serum PSA 26,88 ng/ml, prostate volume 54,33 ml, PSA density 0,39. In non-catheterized group the average age were 66,32 years old, serum PSA 16,58 ng/ml, prostate volume 53,94 ml, PSA density 0,33. Regression test showed that serum PSA could be used as a predictor of prostate volume (F=12,830; p < 0,001); in non-catheterized group it was stronger (F=12,989; p<0,001) than in catheterized group (F=6,814; p<0,01). The accuracy of serum PSA as a prostate volume predictor based on Receiver Operating Curve (ROC) as indicated by Area Under the Curve (AUC), in the catheterized group was 0,678 - 0,725 (p<0,001); in non-catheterized group was 0,723 - 0,784 (p<0,001). Conclusion: Serum PSA could be used as a predictor of prostate volume in patients with BPH wether catheterized or not. This predictor function is stronger in non-catheterized patients. Catheter has the effect of lowering the function of serum PSA as a prostate volume predictor in patients with BPH.